Características epidemiológicas asociadas a ansiedad y depresión en estudiantes de medicina humana de la Universidad Nacional de la Amazonia Peruana, Iquitos 2023 - Padilla Garcia, Sariah Iliana (2024)
The importance of mental health is indisputable for all people, but charges a particularly prominent role in certain groups, such as medical students. Future doctors experience significant academic and emotional challenges as they advance in their training process. For this reason, the objective of this work is to determine the epidemiological characteristics associated with anxiety and depression in human medicine students of the National University of the Peruvian Amazon, Iquitos 2023. For this reason, an observational-annal and transverse study was developed, having as Sample 203 medical students. Concluding that 21.18% of the students presented anxiety, observing that suffering from migraine, being dissatisfied with academic performance, having suffered from teaching abuse and having a relative who suffers from anxiety or depression or other mental disorder in addition to some advanced, progressive disease or incurable present statistically significant association with the presence of anxiety (p <0.05). Likewise, it was observed that 51.72% of the students have depression, the characteristics associated with the presence of depression were the age of 17 to 24 years, female sex, be single, be a first -year student and the seventh year/boarding school, Living with a couple, having financing whether family or own resources, having family charge, having always insufficient or sometimes insufficient family income, suffering from migraine, not carrying out recreational/extracurricular activities, being dissatisfied with academic performance, having received abuse teacher and not perform healthy coping skills such as seeking support (p <0.05).